German language proficiency among students of business and management in the Czech Republic and its perception: The importance of German language skills on the labour market and the role of universities in foreign language training - Marek Zinecker (DANUBE: Law, Economics and Social Issues Review, 2014)
This paper presents the results of an empirical study designed to map German language proficiency among students at Czech universities of business and management. The results of this empirical survey can be summarised as follows. First, the ability of students at Czech universities of business and management to communicate in German is poor, and exceeds the general German language proficiency of the Czech population only to an insignificant extent. Second, the school environment (the opportunity to learn the language, compulsory subject, language study motivation) has a decisive influence on the respondents' ability to communicate in German. Third, nearly three-quarters of the respondents perceive German as a language that is very or rather important for their profession and career growth. Fourth, almost two-thirds of the respondents consider the role played by a university of business and management in the improvement of German language proficiency rather or very important. In conclusion, the study proposes directions for the potential development of the national educational system in the area of German language proficiency of university graduates in business and management in the Czech Republic, with an emphasis on the concept of content and language integrated learning (CLIL). We believe that the survey results are also very important from the point of view of enterprises operating in the Czech Republic because of the very close economic relations between the Czech Republic and German-speaking countries.
Keywords: 330; Content and Language Integrated Learning (CLIL); German Language Proficiency; Students of Business and Management; Foreign Language Training at Universities